Crafting Static Infographic Teaching Materials on Physical Inheritance and Evolution in Phase F to Enhance PPRA - Anggun, Diah Putri; Monika, Thasya; Samiha, Yulia Tri; Asnilawati, Asnilawati (UIN Syekh Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2024)
Static infographics as a teaching material that can be used as a way to increase students' learning motivation. This study discusses the development of teaching materials in the form of static infographics of organ system material in the human body in Phase F for PPRA reinforcement. The purpose of this study was to produce valid and practical static infographic teaching materials. Based on the results of interviews with one of the Biology teachers in the teaching and learning process on the material of organ systems in the human body only uses teaching materials in the form of PowerPoint and videos taken from YouTube. As a result, students' interest in the material of the organ system in the human body is still low. The material used in this static infographic is in the form of enrichment material containing PPRA values, namely the value of being civilized (ta'abbud), balanced (tawazun), dynamic and innovative (tathawwur waibtikar), and tolerance (tasamuh). This research uses the Research and Development method, which is a study to create, produce, and develop a new product. This research uses the Plomp model in 2013 which is limited to the prototype stage. Data collection techniques were carried out using interviews, observation, documentation, and questionnaires given to respondents. Based on the results of the study, the average value of material experts, media experts, and linguists was obtained with a value of 3.61 a very valid category. And for the practicality questionnaire assessment with an average score of 3.64 with a very practical category. The results of these responses that static infographic teaching materials are valid and practical for use in the learning process.